IN SITU GEL FORMULATION OF POTASSIUM NITRATE: A NOVEL APPROACH TO TREAT DENTIN HYPERSENSITIVITY - DABHADKAR, MEGHNA; KULKARNI, MADHUR (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of the present study was to develop an in situ gelling formulation of potassium nitrate for the treatment of dentin hypersensitivity (DH). Methods: Formulation was optimized using 32 full factorial design, wherein the concentration of two gelling agents, poloxamer 407 and chitosan (90% deacetylation) were the independent variables and formulation viscosity and gelation time were dependent variables. The trial formulations were evaluated for pH, spreadability, drug content, adherence time, and in vitro drug release, apart from viscosity and gelation time. Results: The optimized formulation containing 22% of poloxamer 407 and 0.5 % of chitosan exhibited a gelation time of less than 150 s, a viscosity of about 2450 cps, and thermoreversible sol-gel transition behavior. The novel in situ gel showed a pH of 4.58, and spreadability as 5.55 g. cm/s and adherence time 4.3 h. The formulation could sustain the drug release over a period of 4 h and it was found to be 81.83±1.03%. Accelerated stability studies conducted over 3 mo duration ensured good physical and chemical stability of the formulation. Conclusion: The optimized in situ gel formulation of potassium nitrate in the sol state is expected to allow easy and site-specific administration on the sensitive tooth. Upon application, the temperature-sensitive sol would get converted to a gel that would improve its retention time on the sensitive tooth and extend the duration of therapeutic action by sustaining the drug release.